Probing the symmetric Higgs portal with di-Higgs boson production - Englert, Christoph; Jaeckel, Joerg (Physical review, 2019)
A coupling of a scalar, charged under an unbroken global U(1) symmetry, to the Standard Model via the Higgs portal is one of the simplest gateways to a dark sector. Yet, for masses mS≥mH/2 there are few probes of such an interaction. In this note, we evaluate the sensitivity to the Higgs portal coupling of di-Higgs boson production at the LHC as well as at a future high-energy hadron collider, FCC-hh, taking into account the full momentum dependence of the process. This significantly impacts the sensitivity compared to estimates of changes in the Higgs coupling based on the effective potential. We also compare our findings to precision single Higgs-boson probes such as the cross section for vector-boson-associated Higgs production at a future lepton collider, e.g., FCC-ee, as well as searches for missing energy-based signatures.
Gesehen am 29.01.2020